Comprehensive Histopathological Examination and Breast Cancer: An Institutional Analysis - Rana, Manjit Kaur; Mahajan, M K (Annals of Pathology and Laboratory Medicine, 2020)
Background: The histological patterns and other microscopic parameters play important role in the therapeutic management and assessment of the prognosis of the carcinoma breast. As this carcinoma shows heterogeneity, a careful gross examination followed by a more detailed examination of tissue sections is the backbone of the histopathological analysis. Methods: Total of 103 cases of breast carcinoma were included in the study. Histopathological reports along with detailed gross examination findings were re-assessed for various histological patterns and associated features. Data obtained was analysed. Result: Gross examination findings showed 9.4% multiplicentricity of the tumor. Histopathology revealed infiltrating ductal cell carcinoma not otherwise specified (IDC NOS) as most common histologic type (77.6%), I as common grade (45.8%) and IIA as common stage (28%) with other unique microscopic characteristics. Conclusion: Gross findings were more or less similar with results shown in the literatures except 9.4% multiple invasive pattern of the tumor. Different histopathological findings were papillary carcinoma as second common histogical pattern, histologic grade I as common grade, evidence of lymphovascular invasion less common than perineural invasion. In addition atypical ductal hyperplasia was seen associated with papillary carcinoma commonly and desmoplasia with N0 tumor.